1989
DOI: 10.1016/0014-5793(89)81527-3
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of islet amyloid polypeptide in response to glucose

Abstract: The content of islet amyloid polypeptide (IAPP) in isolated rat pancreatic islets was determined by a radioimmunoassay. Reverse-phase high-performance liquid chromatography analysis revealed that a main peak of IAPP immunoreactivity in the extracts from the islets corresponded to a synthetic rat IAPP. Secretion of IAPP from the cells is regulated by the extracellular glucose concentration. Thus, IAPP may be a novel regulator for glucose homeostasis and changes in the secretion perhaps relate to insular amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 15 publications
(4 reference statements)
3
48
0
Order By: Relevance
“…In advanced type II diabetes, local amylin excesses (24) could further contribute to the inability of the ,B cell to accurately sense and respond to normal variations in glucose levels. Although it is impossible to precisely measure the local concentration of amylin as it is secreted from the 3 cell, local concentrations up to 10-8 M have been estimated (25,26). Effects seen in this study were robust at this concentration, as well as at lower and higher concentrations (0.1-500 nM).…”
Section: Resultsmentioning
confidence: 60%
“…In advanced type II diabetes, local amylin excesses (24) could further contribute to the inability of the ,B cell to accurately sense and respond to normal variations in glucose levels. Although it is impossible to precisely measure the local concentration of amylin as it is secreted from the 3 cell, local concentrations up to 10-8 M have been estimated (25,26). Effects seen in this study were robust at this concentration, as well as at lower and higher concentrations (0.1-500 nM).…”
Section: Resultsmentioning
confidence: 60%
“…The isolated-perfused pancreas, primary islets, or b-cell models have shown that amylin secretion can be stimulated by many factors, including glucose, arginine, and fatty acids, and that amylin secretion tracks insulin secretion (Kanatsuka et al, 1989;Ogawa et al, 1990;Qi et al, 2010). Pancreatic b cells are the major source of circulating plasma amylin, which ranges from 3-5 pM in the fasting state to postprandial concentrations of 15-25 pM (Lutz, 2006;.…”
Section: B Amylin Expression Secretion and Metabolismmentioning
confidence: 99%
“…IAPP is synthesized primarily in the pancreatic ␤-cell, where it is colocalized with insulin in secretory granules (4,5) and is released along with insulin in response to stimulation by ␤-cell secretagogues such as glucose (6,7). The physiological function of IAPP has not been determined, although effects on insulin action (8) and secretion (9), gastric emptying (10), and food intake (11) have all been suggested.…”
mentioning
confidence: 99%